2010
DOI: 10.1211/jpp.62.07.0010
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective pharmacokinetic–pharmacodynamic modelling of carvedilol in aNG-nitro-l-arginine methyl ester rat model of secondary hypertension

Abstract: Carvedilol showed enantioselective non-linear pharmacokinetic properties in both groups. An enhanced hypotensive activity of carvedilol was found in L-NAME hypertensive rats compared with control rats, which may be explained by the greater potency of carvedilol for sympathetic vascular tone inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 43 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…Spectral analysis of blood pressure recording in rats has established that variability at the low frequency (LF) domain is affected by vascular sympathetic tone and endothelial-derived NO and the normalization of LF by high frequency (HF) variability (LF/HF ratio) represents a validated marker of sympathetic vascular activity in preclinical and clinical studies [57][58][59][60]. By using an inhibitory indirect physiological model, we have found a good relationship between racemic carvedilol plasma concentrations and their effect on the LF/HF ratio, suggesting that PK/PD modeling could be a powerful tool for the assessment of the effects of third-generation β-blockers on sympathetic vascular activity [31,32]. In a previous study, a greater sympatholytic activity of carvedilol was found in L-NAME treated rats than in control normotensive rats, evidenced by a lower concentration that produces 50% of vascular sympathetic tone inhibition (IC 50 ) in the hypertensive group [31].…”
Section: Preclinical Pk/pd Modelingmentioning
confidence: 91%
See 4 more Smart Citations
“…Spectral analysis of blood pressure recording in rats has established that variability at the low frequency (LF) domain is affected by vascular sympathetic tone and endothelial-derived NO and the normalization of LF by high frequency (HF) variability (LF/HF ratio) represents a validated marker of sympathetic vascular activity in preclinical and clinical studies [57][58][59][60]. By using an inhibitory indirect physiological model, we have found a good relationship between racemic carvedilol plasma concentrations and their effect on the LF/HF ratio, suggesting that PK/PD modeling could be a powerful tool for the assessment of the effects of third-generation β-blockers on sympathetic vascular activity [31,32]. In a previous study, a greater sympatholytic activity of carvedilol was found in L-NAME treated rats than in control normotensive rats, evidenced by a lower concentration that produces 50% of vascular sympathetic tone inhibition (IC 50 ) in the hypertensive group [31].…”
Section: Preclinical Pk/pd Modelingmentioning
confidence: 91%
“…PK/PD properties of carvedilol have been compared in L-NAME hypertensive rats and normotensive rats by means enantioselective PK-PD modeling [31]. While S-carvedilol plasma levels were correlated with the chronotropic response by using an effect compartmental model, total racemic concentrations of carvedilol were related with the blood pressure lowering response considering that the R-enantiomer shows α-blocking activity [31].…”
Section: Preclinical Pk/pd Studies With β-Blockersmentioning
confidence: 99%
See 3 more Smart Citations